QUR'AN HADITH TEACHER'S STRATEGIES IN ENHANCING VOCABULARY UNDERSTANDING USING CROSSWORD PUZZLE MEDIA - Novalyo Suranda; Zurifah Nurdin; Dayun Riadi (El Midad, 2025)
This study aims to determine the strategies used by Al-Qur'an Hadith teachers in providing understanding of vocabulary using Crossword Puzzle media, to determine the learning process of Al-Qur'an Hadith using Crossword Puzzle media, and to determine the evaluation of Al-Qur'an Hadith teachers' strategies in providing understanding of vocabulary using Crossword Puzzle media for fifth grade students of Al-Qur'aniyah Elementary School, South Bengkulu. This study is a descriptive qualitative study. MI Al-Qur'aniyah, South Bengkulu, conducted this study. The research data were collected through observation, interviews, and documentation. The results of this study indicate that teachers utilise crossword puzzle media to make learning more engaging, thereby enabling students to better understand and retain the vocabulary of the Al-Qur'an. By using Crossword Puzzle media, teachers can develop students' creativity in understanding and applying the Qur'anic vocabulary in different contexts. Research indicates that the use of Crossword Puzzle media can enhance students' learning outcomes in the Qur'an and Hadith subjects. The strategy employed by Al-Qur'an Hadith teachers at MI Al-Qur'aniyah involves creating learning devices and lesson plans through lecture, discussion, and Q&A methods. In the evaluation of the learning process using inquiry strategies and crossword puzzle media, the following aspects: 1) Student involvement. 2) Critical thinking skills. 3) Creativity. 4) Collaboration